Avances en ortodoncia interceptiva: invisalign firts revisión bibliográfica - Buenaño Naula, Valeria Estefanía (2025)
Invisalign First [IF] is an interceptive orthodontic treatment, it is characterized by being invisible and removable, specifically designed for children between 6 and 12 years old. It appeared more than five years ago and promises several aesthetic and functional benefits compared to traditional orthodontics. Objective: To analyze the efficacy of Invisalign First for treating malocclusion problems in children aged 6 to 12 years through the analysis of existing evidence. Materials and Methods: A systematic review of scientific publications was conducted in databases such as PubMed, SciELO, and Google Scholar using MeSH terms, forming search lines, and applying inclusion and exclusion criteria. Results: A total of 408 articles were identified and 18 were included in the final detailed review. Prospective, retrospective studies and case reports showed favorable results in the malocclusions and other pathologies treatment. Conclusion: The review of the existing evidence has allowed it to conclude that (IF) is an effective technique for the treatment of malocclusions in children aged 6 to 12 years, allowing early correction that prevents future complications.